Yield and Chemical Composition of Fodder Guar (Cyamopsis tetragonoloba L.) as Affected by Harvesting Stage and Zinc Application - Pandey, A.K.; Singh, M.; Thakur, S.S.; Kumar, R.; Meena, R.K.; Basak, N.; Meena, V.K.; Kushwaha, M.; Tamta, A.; Subrahmanya, D.J. (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted to study the performance of guar (Cyamopsis tetragonoloba L.) fodder as affected by stage of harvesting and zinc application with four stages of harvesting (50, 60, 70 and 80 DAS) and four levels of ZnSO4 application (Control, 10 kg ZnSO4/ha, 20 kg ZnSO4/ha, and 0.5% ZnSO4 spray 30 DAS) with three replications in Split Plot Design. The green fodder yield and DM yield increased at harvest upto 80 DAS and zinc application @ 20 kg/ha while OM content was significantly higher at 50 DAS. The maximum CP level in the fodder was obtained when the crop was harvested at 60 DAS with application of ZnSO4 @ 20 kg/ha. However, the contents of DM, EE, ash contents were higher due to harvesting of crop 80 DAS and application of ZnSO4 @ 20 kg/ha over other treatments. NDF and ADF were recorded significantly higher at 80 DAS while hemicellulose at 70 DAS without any application of Zn (control). However, harvesting at 80 DAS and 20 kg/ha ZnSO4 application was a better combination for yield and quality of guar fodder.